Pengaruh Citra Merek, Kualitas Produk, dan Harga terhadap Keputusan Pembelian Gen Z Pada Produk Jiniso - Aura Annasty Syakurani; Aditya Liliyan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
The research aims to investigate how brand image, price, and product quality affect the purchase decisions of Generation Z consumers toward Jiniso, a notable local fashion brand in Indonesia. Utilizing an associative quantitative method, this study enables a systematic empirical evaluation of the interconnections among these variables. The participants consisted of 108 Generation Z women who had previously bought Jiniso products, chosen via purposive sampling. Information was gathered through an online questionnaire employing a five-point Likert scale, subsequently analyzed with multiple linear regression via IBM SPSS Statistics 25 software. Results show that brand image exerts no meaningful influence on purchase decisions, while price and product quality provide substantial positive contributions. An Adjusted R² figure of 0.499 indicates that these three factors together account for 49.9% of the variance in purchase decisions. These outcomes highlight Generation Z consumers' inclination to favor concrete product features and financial worth rather than symbolic brand views, thereby delivering valuable guidance for promotional tactics of local fashion brands.